The Role of Animation Learning Media towards Increasing Interest in Learning Mathematics - Fella Nur Azizah; Asep Jihad; Juariah Juariah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to see the role of animated learning media in increasing students' interest in learning mathematics. This study uses the Systematic Literature Review (SLR) method in which researchers examine, evaluate and describe relevant previous studies. The results showed that the use of interactive and innovative learning media could increase students' interest in learning in the field of mathematics. Animated learning media can be used as an innovation in learning mathematics. One of the easy-to-use animated learning media applications is PowToon